Geographical component of the chronotope of the English scientific discourse and the forms of its representation - Tserkovnov, S. A.; Svoikin, K. B. (Vestnik Samarskogo universiteta. Istorii͡a︡, pedagogika, filologii͡a, 2024)
The article deals with the geographical component of the chronotope of the English scientific discourse. The authors identify the forms of geographical representation of the chronotope of scientific discourse, determine the degree of identifiability of these forms, and also explore the significance of the geographical component of the chronotope in the categorization of scientific discourse. 112 English scientific articles from 4 disciplinary areas (linguistics, literature, economics, biology) published in scientific periodicals are used as practical material. In the course of the study, the authors discover three types of geographical markers used in the texts of scientific discourse: the topos of publishing a scientific work, the topos of writing a scientific work, and the topos of the object, subject and material of the study (intratext topos). The authors analyze the degree of identification of each type of markers in scientific texts, and also conduct a comparative analysis of these markers. The level of coincidence of the topos of the publication, the topos of writing and the topos of the object of study is investigated. As a result of the analysis, the authors observe a low level of interdependence of geographical markers, which suggests that the geographical component of the chronotope is of little importance for the categorization of a scientific text. On the basis of the data obtained, the authors believe that the geographical markers of a scientific text should be perceived as elements of the formal and technical design of a scientific text, and not as its constituent characteristic. In conclusion, the authors give a number of directions for further considering the constituent topos in the chronotope of scientific discourse, in particular, its disciplinary and thematic component.